Sylvia & Aki - Conkling, Winifred (<> Yearling Book, 2013)
At the start of World War II, Japanese-American third-grader Aki and her family are sent to an internment camp in Poston, Arizona, while Mexican-American third-grader Sylvia's family leases their Orange County, California, farm and begins a fight to stop school segregation
Includes bibliographical references (p. 145-149)
Pt. 1. California and Arizona 1941 -- pt. 2. California and Arizona 1944-1945 -- Epilogue. California 1955
Keywords: Poston Relocation Center (Ariz.) / Juvenile fiction; Poston Relocation Center (Ariz.) / Fiction; Poston Relocation Center (Ariz.); Evacuation and relocation of Japanese Americans (United States : 1942-1945); Geschichte 1900-2000; Geschichte 1941-1955; Race relations / Juvenile fiction; Segregation in education / Juvenile fiction; Japanese Americans / Evacuation and relocation, 1942-1945 / Juvenile fiction; Mexican Americans / Juvenile fiction; Farm life / California / Juvenile fiction; Race relations / Fiction; Segregation in education / Fiction; Japanese Americans / Evacuation and relocation, 1942-1945 / Fiction; Mexican Americans / Fiction; Farm life / California / Fiction; Farm life; Japanese Americans; Mexican Americans; Race relations; Segregation in education; Geschichte; Zweiter Weltkrieg; Schulbildung; Segregation -- Soziologie; Internierungslager; Japaner; Widerstand; Orange County (Calif.) / History / 20th century / Juvenile fiction; Orange County (Calif.) / History / 20th century / Fiction; California; California / Orange County; USA; Kalifornien; Kinderbuch